2011
DOI: 10.1097/tp.0b013e3182094a5a
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes Are Associated With Loss of Kidney Graft Function and Interstitial Fibrosis and Tubular Atrophy: Diagnosis Versus Prediction

Abstract: An IF/TA gene expression signature was identified, and it was useful for diagnosis but not prediction. However, gene expression profiles at 3 months might predict IF/TA progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…[24][25][26][27]38 miR-142-3p expression has also been associated with tubular atrophy and interstitial fibrosis of renal transplants. 22 Moreover, miR-142-3p was overexpressed in B lymphocytes from the blood of operationally tolerant patients, and this analysis performed in peripheral blood does not exclude a different expression profile within the graft itself. In addition, we did not find any correlation between miR-142-3p expression and posttransplantation time and did find miR-142-3p expression to be stable over time ( Figure 2C); these results indicate that miR-142-3p is independent of post-transplantation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27]38 miR-142-3p expression has also been associated with tubular atrophy and interstitial fibrosis of renal transplants. 22 Moreover, miR-142-3p was overexpressed in B lymphocytes from the blood of operationally tolerant patients, and this analysis performed in peripheral blood does not exclude a different expression profile within the graft itself. In addition, we did not find any correlation between miR-142-3p expression and posttransplantation time and did find miR-142-3p expression to be stable over time ( Figure 2C); these results indicate that miR-142-3p is independent of post-transplantation time.…”
Section: Discussionmentioning
confidence: 99%
“…18 Numerous studies have reported on the differential expression of miRNA in physiologic disorders or diseases, 19,20 and miRNA has been found to be modulated in biopsy specimens from kidney transplant recipients. [21][22][23] In this study, we investigated whether miRNA is modulated in the blood of patients with operational tolerance compared with a cohort of patients with stable graft function under classic immunosuppression.…”
mentioning
confidence: 99%
“…Scian et al demonstrated that genes upregulated in IFTA are primarily involved in pathways related to T-cell activation, NK cell-mediated cytotoxicity, and programmed cell death [24] . To date, there is no corroborating evidence for NK or NKT cells being the cause of IFTA after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Renal biopsy tissue can also be used for unbiased approaches such as microarray analyses, which may yield diagnostic molecular signatures (213,(369)(370)(371)(372)(373)(374). This ''molecular microscope'' has been shown to improve the diagnosis of rejection but also to reflect molecular alterations in fibrosis (375)(376)(377)(378).…”
Section: Diagnosis Of Renal Fibrosismentioning
confidence: 99%